Pedagogic appropriations and experiences in Philosophy and Infancy in Colombia (2017)
This article presents a theoretical and reflexive construction which contains a state of art for Philosophy for Children in Colombia, resulting from the compilation of articles published in specialized journals and book chapters. Reflections and experiences that show the importance of teaching philosophy in formal and nonformal institutions are highlighted. In consequence, there are three categories worked: philosophical education, thinking the thought and experiences (which are structured based on the program of Mathew Lipman and other authors, such as Diego Pineda and Walter Kohan), that proves the transformation of thinking and the innovations of some educational practices in the country. This article is product of one of the objectives of the research project SGI 16162, a thorough study that outlines and acknowledges academic production in Colombia to enlighten researchers, teachers and students about different approaches or experiences surrounding a program that relates philosophy with childhood.